2017
DOI: 10.1097/shk.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Phototherapy to Treat Carbon Monoxide Poisoning in Rats

Abstract: Background Carbon monoxide (CO) poisoning is a common cause of poison-related mortality. CO binds to hemoglobin in the blood to form carboxyhemoglobin (COHb), impairing oxygen delivery to peripheral tissues. Current treatment of CO poisoned patients involves oxygen administration to rapidly remove CO and restore oxygen delivery. Light dissociates CO from COHb with high efficiency. Exposure of murine lungs to visible laser-generated light improved the CO elimination rate in vivo. The aims of this study were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…First, the laser directly dissociates CO from the blood. In murine models, Zazzeron et al [ 22 , 23 ] found that direct illumination of the lungs could facilitate the dissociation of CO from hemoglobin, thus increasing the concentration of exhaled CO. This finding indicates that the laser beam is capable of counteracting dissolved CO in situations involving acute intoxication or occult exposure.…”
Section: Discussionmentioning
confidence: 99%
“…First, the laser directly dissociates CO from the blood. In murine models, Zazzeron et al [ 22 , 23 ] found that direct illumination of the lungs could facilitate the dissociation of CO from hemoglobin, thus increasing the concentration of exhaled CO. This finding indicates that the laser beam is capable of counteracting dissolved CO in situations involving acute intoxication or occult exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For the generation of an MI model, 8-week-old male Wistar rats (n ¼ 45) were used. Rats weighing 250-280g were anaesthetized with intraperitoneal ketamine (100 mg/kg) and xylazine (10 mg/kg) [21,22], and a small incision was made in the fourth intercostal space. After that, the heart was then gently brought out through the window.…”
Section: Rat Model Of Acute Myocardial Infarctionmentioning
confidence: 99%
“…Red Light Therapy at wavelengths of 630 to 660nm (FDA approved but not for CO poisoning) a. releases CO from heme proteins b. works invasively inside lungs [Zazzeron 2017] or externally, with light against skin c. other applications included relieving muscle pain, cramps, rashes, cough, headaches, and sore throats 5.6 Sunbathing in natural or artificial light (the latter is FDA approved for treatment of hyperbilirubinemia) a. hastens excretion of free CO through skin; enhanced by ingesting riboflavin [Vreman 2009] b. increases vitamin D synthesis and, via UVc radiation, kills viruses on skin and other surfaces Mechanical ventilation combined with high flow or hyperbaric oxygen are not recommended because they are not effective for survivors of CO poisoning. In a series of 81 cases reported from Taiwan, 50.6% suffered bad outcomes, including 11% who died [Kao 2009].…”
Section: 5mentioning
confidence: 99%